2020 International Joint Conference on Neural Networks (IJCNN) 2020
DOI: 10.1109/ijcnn48605.2020.9206647
|View full text |Cite
|
Sign up to set email alerts
|

GA-MSSR: Genetic Algorithm Maximizing Sharpe and Sterling Ratio Method for RoboTrading

Abstract: Foreign exchange is the largest financial market in the world, and it is also one of the most volatile markets. Technical analysis plays an important role in the forex market and trading algorithms are designed utilizing machine learning techniques. Most literature used historical price information and technical indicators for training. However, the noisy nature of the market affects the consistency and profitability of the algorithms. To address this problem, we designed trading rule features that are derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…Zhang, Z. proposed a genetic algorithm using a crossover of technique indicators as input. It successfully outperformed some of the traditional trading strategies [91].…”
Section: Other Deep Learning Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Zhang, Z. proposed a genetic algorithm using a crossover of technique indicators as input. It successfully outperformed some of the traditional trading strategies [91].…”
Section: Other Deep Learning Methodsmentioning
confidence: 97%
“…Table 20 shows the details of the papers that used the Sharpe ratio as a performance metric. In this table, papers [14,18] used a CNN-based model; papers [71,75] used a DNN-based model; papers [77] and [82] used a reinforcement learning-based model; and papers [84,88,90,91] used other deep learning methods. It could be found that papers [75,84,91] performed best, which used a DNN model, and Sharpe ratio was in the range of 5-10.…”
Section: Analysis Based On Sharpe Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Trillions of dollars are traded every day on financial markets [1,2]. The stock market is often deemed volatile and unpredictable, making it a challenge to maximise profit and hedging losses.…”
Section: Introductionmentioning
confidence: 99%